Evaluation of clogged hydropower plant trash rack losses - Hribernik, Aleš (Strojniški vestnik, 2020)
A trash rack is applied in front of the turbine to restrict the entrance of significantly sized material present in the water. It obstructs the free flow, and produces energy-losses by generating eddies induced partially by the trash rack bars and partially by the debris collected on it. While the additional static forces due to debris accumulation are considered in the trash rack design process, the debris caused energy losses taking place during plant operation are usually neglected, although a rather simple model was developed to account for them. However, the long term application of this model demands an extensive set of trash rack clogging data and, therefore, no such application has been documented so far. Thus, an analysis was performed to acquire the debris accumulation intensity with time and to evaluate the extra energy losses they caused. Data on one year operation of a hydropower plant aggregate i.e. flow rate and trash rack head losses measured at 15 minute intervals, were acquired and used to build a rack clogging model. Using this model, it was possible to distinguish clearly between debris and rack structure caused head losses, and to analyse different cleaning strategies. It was shown that cumulative debris contributed to almost one half of head losses although the rack was cleaned frequently. This shows clearly that debris caused head losses may not be neglected, moreover, debris removal has to be planned carefully and carried out efficiently. Analyses of acquired data confirmed that incomplete debris removal increased head losses by 18 %, and proved how important regular and thorough rake cleaning is. Moreover, it was found out that the actually applied periodical rake cleaning was not optimal, and that the circumstances required cleaning strategy performed much better. It resulted in similar head losses, while the number of rack cleanings was reduced by 60 %.
Keywords: debris; energijske izgube; head losses; hidroelektrarne; hydropower plants; plavine; rešetke; trash racks; učinkovitost in optimalna strategija čiščenja rešetke